Stereoscopic vascular models of the head and neck: A computed tomography angiography visualization. Issue 2 (30th April 2015) - Cui, Dongmei; Lynch, James C.; Smith, Andrew D.; Wilson, Timothy D.; Lehman, Michael N.
Abstract : Computer‐assisted 3D models are used in some medical and allied health science schools; however, they are often limited to online use and 2D flat screen‐based imaging. Few schools take advantage of 3D stereoscopic learning tools in anatomy education and clinically relevant anatomical variations when teaching anatomy. A new approach to teaching anatomy includes use of computed tomography angiography (CTA) images of the head and neck to create clinically relevant 3D stereoscopic virtual models. These high resolution images of the arteries can be used in unique and innovative ways to create 3D virtual models of the vasculature as a tool for teaching anatomy. Blood vessel 3D models are presented stereoscopically in a virtual reality environment, can be rotated 360° in all axes, and magnified according to need. In addition, flexible views of internal structures are possible. Images are displayed in a stereoscopic mode, and students view images in a small theater‐like classroom while wearing polarized 3D glasses. Reconstructed 3D models enable students to visualize vascular structures with clinically relevant anatomical variations in the head and neck and appreciate spatial relationships among the blood vessels, the skull and the skin. Anat Sci Educ 9: 179–185. © 2015 American Association of Anatomists.